The effect of triacylglycerol-fatty acid positional distribution on postprandial metabolism in subcutaneous adipose tissue. - Summers, L; Fielding, B; Ilic, V; Quinlan, P; Frayn, K (1998)
We hypothesized that fatty acids at the sn-2 position of chylomicron triacylglycerol are preferentially released into the venous plasma (rather than being taken up and stored in the adipocytes) after hydrolysis by lipoprotein lipase (EC 3.1.1.34) in adipose tissue. Arteriovenous differences across adipose tissue were studied in eight healthy subjects on two occasions for 6 h after ingestion of different structured triacylglycerols rich in palmitic acid either at the sn-2 or the sn-1,3 positions. In particular the specific fatty acids making up lipoprotein fractions and plasma non-esterified fatty acids were analysed. After the different meals there were no differences between either postprandial arterialized or venous plasma metabolite concentrations. Chylomicron triacylglycerol extraction in adipose tissue was the same following the two types of fat. There was no difference between the specific fatty acid composition of the postprandial non-esterified fatty acid release from adipose tissue after ingestion of the two triacylglycerols, indicating that there was no preferential release of a saturated fatty acid at the sn-2 position.